2020
DOI: 10.3390/biom10091266
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MHC Regulation Using Polycyclic Polyprenylated Acylphloroglucinols Isolated from Garcinia bancana

Abstract: Modulation of major histocompatibility complex (MHC) expression using drugs has been proposed to control immunity. Phytochemical investigations on Garcinia species have allowed the isolation of bioactive compounds such as polycyclic polyprenylated acylphloroglucinols (PPAPs). PPAPs such as guttiferone J (1), display anti-inflammatory and immunoregulatory activities while garcinol (4) is a histone acetyltransferases (HAT) p300 inhibitor. This study reports on the isolation, identification and biological charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…We previously found that STAT1 helps Tim-3 to transduce signal (7). The STAT1-CIITA signaling pathway is involved in the regulation of MHC-II transcription (18)(19)(20). To test whether Tim-3 inhibits CIITA expression via STAT1, we first examined the Tim-3 and STAT1 signal to CIITA.…”
Section: Stat1 Acts As a Signaling Adaptor For Tim-3-mediated Suppres...mentioning
confidence: 99%
“…We previously found that STAT1 helps Tim-3 to transduce signal (7). The STAT1-CIITA signaling pathway is involved in the regulation of MHC-II transcription (18)(19)(20). To test whether Tim-3 inhibits CIITA expression via STAT1, we first examined the Tim-3 and STAT1 signal to CIITA.…”
Section: Stat1 Acts As a Signaling Adaptor For Tim-3-mediated Suppres...mentioning
confidence: 99%
“…Approaches to circumvent EC activation and dysfunction using treatment with cyclic nitroxides, namely, 4-methoxy tempol (4-MetT), showed significant inhibition or reversal of the inflammatory pattern mediated by Serum Amyloid A on cultured ECs, but this remains to be validated in vivo [ 16 ]. Polyphenols extracted from medicinal plants also provide interesting drugs to decrease inflammation and immunoregulation at the EC level [ 17 ]. Polyphenols display protective effects on inflammatory and permeability markers as well as monocyte recruitment on cerebral ECs exposed to hyperglycemic condition [ 4 ], indicating their relevance for pharmacological strategies aiming to limit cerebrovascular disorders in diabetes.…”
Section: Endothelial Cells As Therapeutic Targets and Sources Of Non-...mentioning
confidence: 99%
“…A compound like Ob-C (and likely Gt-K) which targets HSPA8, could thus be useful to regulate immunity, in addition to enhancing the effects of anticancer drugs. For example, the related compound Gt-J has been found to trigger a strong immunomodulation, inducing a marked decrease of major histocompatibility complex (MHC class II) molecules on endothelial cells [ 94 ] and the related compound Gt-F has revealed also immunoregulatory activities, downregulating the expression of several MHC molecules at the surface of human primary endothelial cells upon inflammation [ 6 ]. Altogether, this information should encourage further study of the immunoregulatory effects of Ob-C and its capacity to interact with HSPA8.…”
Section: Molecular Targets Of Ob-c and Gt-kmentioning
confidence: 99%
“…The PPAPs database include more than 850 structures, with molecules showing extremely diverse bioactivity profiles [ 4 ]. There are compounds acting as potent modulators of the major histocompatibility complex, such as PPAPs isolated from Garcinia bancana [ 5 ], compounds with anti-adipogenic activity, isolated from Hypericum subsessile [ 6 ], compounds with marked antiparasitic and antimicrobial effects, such as PAPPs identified from the medicinal plant Symphonia globulifera [ 7 ], and PPAPs with anti-depressive and hepatoprotective activities found in the aerial parts of Hypericum scabrum [ 8 ], to cite only a few examples. There are also many compounds with anti-inflammatory, anticancer, antifungal, antibacterial, antiviral, immunoregulatory properties and other bioactivities.…”
Section: Introductionmentioning
confidence: 99%